Chronic Neurophysiological Effects of Repeated Head Trauma in Retired Australian Male Sport Athletes - Pearce, Alan J.; Kidgell, Dawson J.; Tommerdahl, Mark A.; Frazer, Ashlyn K.; Rist, Billymo; Mobbs, Rowena; Batchelor, Jennifer; Buckland, Michael E. (Frontiers in Neurology, 2021)
Aim: This study investigated the somatosensory and corticomotor physiology of retired contact sport athletes with a history of repeated concussion/subconcussion head trauma. Methods: Retired male athletes with a history of playing contact sports and repeated head trauma (n=122) were divided into two groups: those who expressed concerns regarding their mental and cognitive health (‘symptomatic’: n=83), and those who did not express any ongoing concerns (‘asymptomatic’: n=39). Both groups were compared to age-matched male controls (n=50) with no history of concussions or participation in contact sports, an absence of self-reported cognitive or mood impairments. Transcranial magnetic stimulation (TMS) and vibrotactile stimulation were used to assess corticomotor and somatosensory pathways respectively. TMS and vibrotactile stimulation were correlated to self-reported responses using the Fatigue and Related Symptom Survey. Linear regression was used to associate concussion history with TMS, somatosensory variables. Results: Significant differences were found in symptom survey scores between all groups (p<0.001). TMS showed significant differences between the ‘symptomatic’ and control groups for intracortical inhibition and paired pulse TMS measures. Somatosensory measures showed significant differences for reaction time (p<0.01) and reaction time variability (p<0.01) between the ‘symptomatic’ group to the ‘asymptomatic’ and control groups. For other somatosensory measures, the ‘symptomatic’ measures showed differences to the ‘control’ group. Correlations showed significant associations between severity of symptom reporting with TMS and somatosensory measure, and regression revealed the number of concussions reported was shown to have significant relationships to increased intracortical inhibition and poorer somatosensory performance. Conclusion: This study shows that retired contact sport athletes expressing chronic symptoms showed significant pathophysiology compared to those with no ongoing concerns and non-concussed controls. Further, there is a linear dose-response relationship between number of reported concussions and abnormal neurophysiology. Neurophysiological assessments such as TMS and somatosensory measures represent useful and objective biomarkers to assess cortical impairments and progression of neuropsychological impairment in individuals with a history of repeated head trauma.